(a⁻³(1-a⁻²))/(a⁻²(a⁻²-1))=-a⁻¹
1)(2x - 3)(x+1)>x(в квадрате) +17=
2x(в кавадрате) +2х-3х-3>х(в квадрате) +17
2x(в кавадрате) +2х-3х-3-х(в квадрате) -17>0
х(в квадрате) - х - 20 >0
х(в квадрате) -х - 20=0
D=1-4*(-20)=81
х1= 1+9/2= 5
х2= 1-9/2= -4
(х-5)(х+4)
+ - +
-4 5
ответ: ( - ∞ ;-4)U(5;+ ∞)
2)11-x >= (x+1)в квадрате=
11-х >= х(в квадрате) + 2х+1
11-х - х(в квадрате)-2х-1 >=0
-х(в квадрате) - 3х+10>=0
-х(в квадрате) - 3х+10=0
D=9-4*(-1)*10=49
х1=3-7/-2=2
х2=3+7/-2=-5
+ - +
-5 2
ответ: ( - ∞;-5 ] U [ 2 ; + ∞)
3)-3x <+9x
-3х - 9х < 0
-12х < 0
х > 0
1)(2x - 3)(x+1)>x(в квадрате) +17=
2x(в кавадрате) +2х-3х-3>х(в квадрате) +17
2x(в кавадрате) +2х-3х-3-х(в квадрате) -17>0
х(в квадрате) - х - 20 >0
х(в квадрате) -х - 20=0
D=1-4*(-20)=81
х1= 1+9/2= 5
х2= 1-9/2= -4
(х-5)(х+4)
+ - +
-4 5
ответ: ( - ∞ ;-4)U(5;+ ∞)
2)11-x >= (x+1)в квадрате=
11-х >= х(в квадрате) + 2х+1
11-х - х(в квадрате)-2х-1 >=0
-х(в квадрате) - 3х+10>=0
-х(в квадрате) - 3х+10=0
D=9-4*(-1)*10=49
х1=3-7/-2=2
х2=3+7/-2=-5
+ - +
-5 2
ответ: ( - ∞;-5 ] U [ 2 ; + ∞)
3)-3x <+9x
-3х - 9х < 0
-12х < 0
х > 0
1) A^-3 - A^-5 = 1|A^3 - 1\A^5 = (A^2 - 1) |A^5
2) A^-4 - A^-2 = 1\A^4 - 1|A2 = (1 - A^2 ) \ A^4
3) (A^2 - 1) \ A^5 : (1-A^2) \ A^4 = - (A^2 - 1) *A^4 \ -A^5*(1-A^2) = - 1 | A = (- A^-1)